HUBUNGAN KEMAMPUAN REPRESENTASI DAN DISPOSISI MATEMATIS MATERI FUNGSI SISWA MTs.AL-JIHAD - Rosanti Rosanti; Agung Hartoyo; M. Rifat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstrak This research aims to determine whether there was a relationship of representation and disposition capabilities material mathematical function MTs Al-Jihad students Pontianak. The method used was quantitative method in the form of a correlation study. Subjects were 27 students of class VIII B MTs Al-Jihad Pontianak. The research instrument used, namely a mathematical representation ability tests and questionnaires students' mathematical disposition. The results of data analysis using tu used SPSS both normal and linear data, after a second linear normal and the data was analyzed using product moment correlation test showed that there was no correlation between the ability and disposition mathematical representation in the material functions. Keywords: Conceptual Understanding, Function, Representations